Migration and Transnationalism Pacific Perspectives - Lee, Helen (ANU Press, 2009)
Pacific Islanders have engaged in transnational practices since their first settlement of the many islands in the region. As they moved beyond the Pacific and settled in nations such as New Zealand, the U.S. and Australia these practices intensified and over time have profoundly shaped both home and diasporic communities. This edited volume begins with a detailed account of this history and the key issues in Pacific migration and transnationalism today. The papers that follow present a range of case studies that maintain this focus on both historical and contemporary perspectives. Each of the contributors goes beyond a narrowly economic focus to present the human face of migration and transnationalism; exploring questions of cultural values and identity, transformations in kinship, intergenerational change and the impact on home communities. Pacific migration and transnationalism are addressed in this volume in the context of increasing globalisation and growing concerns about the future social, political and economic security of the Pacific region. As the case studies presented here show, the future of the Pacific depends in many ways on the ties diasporic Islanders maintain with their homelands.